2018
DOI: 10.1016/j.brainresbull.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol modulation of neurocircuit function in the nucleus of the tractus solitarius

Abstract: The nucleus of the tractus solitarius (NTS) is a brain stem region critical to many physiologic processes and has been implicated in addiction to multiple classes of abused drugs, including alcohol (EtOH). That said, the mechanism by which EtOH modulates NTS neurocircuit activity is not well characterized and has yet to be examined utilizing electrophysiologic methods in mouse models of alcohol use disorders. To begin to address this gap in knowledge, we sought to use whole-cell and cell-attached recordings to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Notably, c‐Fos activity was essentially quiescent (less than 5% of controls) in LOFC, dHPC1, and dSub. In contrast to these findings, previous studies have reported increased c‐Fos in several of these brain areas following acute ethanol injections or ethanol drinking, although a history of ethanol vapor exposure resulted in decreased injection‐induced c‐Fos 1,19,26,27 (reviewed by 20 ). These opposing observations can likely be attributed to differences in ethanol dose, route of administration, and duration of exposure.…”
Section: Discussionmentioning
confidence: 76%
“…Notably, c‐Fos activity was essentially quiescent (less than 5% of controls) in LOFC, dHPC1, and dSub. In contrast to these findings, previous studies have reported increased c‐Fos in several of these brain areas following acute ethanol injections or ethanol drinking, although a history of ethanol vapor exposure resulted in decreased injection‐induced c‐Fos 1,19,26,27 (reviewed by 20 ). These opposing observations can likely be attributed to differences in ethanol dose, route of administration, and duration of exposure.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, since NE innervation in the BNST originates mostly in the NTS, we can hypothesize that ethanol increases NE release by acting on the complex network that includes GABA and glutamate inputs to NTS, including the GABA interneurons 48–49 . Concurring with this view, Aimino et al 50 reported that ethanol stimulated NE neurons within the NTS by inhibiting NMDA transmission in mice. In addition, Lee et al reported that the acute administration of ethanol in rats activated the NE neurons originating in the A1‐A2, and C1‐C3 areas as well those originating in the LC 51 …”
Section: Discussionmentioning
confidence: 93%
“…47 Thus, since NE innervation in the BNST originates mostly in the NTS, we can hypothesize that ethanol increases NE release by acting on the complex network that includes GABA and glutamate inputs to NTS, including the GABA interneurons. 48,49 Concurring with this view, Aimino et al 50 reported that ethanol stimulated NE neurons within the NTS by inhibiting NMDA transmission in mice.…”
Section: Ethanolmentioning
confidence: 90%
“…activated norepinephrine neurons in the NTS. 39 Experiment 1 yielded subtle, yet encouraging, signs of ethanol-induced conditioned neuroimmune responses. Experiment 2 aimed at better addressing the potential of IL-6 and IjBa conditioning and pursued possible agedifferences in these responses.…”
Section: Discussionmentioning
confidence: 96%